(untitled) (Ustozlar uchun, 2026)
This article explores the role of art and creativity in O. Henry’s The Last Leaf. The story portrays how artistic expression serves as a medium for human connection, emotional healing, and moral inspiration. Through the character of Behrman, an aging artist, and his final masterpiece, the narrative demonstrates that art can influence life and death, providing meaning beyond aesthetic value. The study highlights the ways in which creativity becomes a tool for empathy, courage, and enduring impact, arguing that the story celebrates the transformative power of human artistic endeavor.